Prescribing high-intensity interval exercise by rpe in individuals with type 2 diabetes: Metabolic and hemodynamic responses - Viana, Ariane Aparecida [UNESP]; Fernandes, Bianca [UNESP]; Alvarez, Cristian; Guimarães, Guilherme Veiga; Ciolac, Emmanuel Gomes [UNESP] (Canadian Science Publishing, 2019)
We tested the hypothesis that rating of perceived exertion (RPE) is a tool as efficient as the heart rate (HR) response to the cardiopulmonary exercise test (CPX) for prescribing and self-regulating high-intensity interval exercise (HIIE), and that metabolic and hemodynamic response to HIIE is superior than to continuous moderate-intensity exercise (MICE) in individuals with type 2 diabetes mellitus (T2DM). Eleven participants (age = 52.3 ± 3 years) underwent HIIE prescribed and self-regulated by RPE (HIIE RPE ; 25 min), HIIE prescribed and regulated by an individual’s HR response to CPX (HIIE HR ; 25 min), MICE prescribed and self-regulated by RPE (30 min) and control (30 min of seated resting) intervention in random order. HR, blood pressure (BP), capillary glucose, endothelial reactivity, and carotid-femoral pulse wave velocity were assessed before, immediately after, and 45 min after each intervention. Exercise HR, speed, and distance were measured during exercise sessions. Twenty-four-hour ambulatory BP was measured after each intervention. Exercise HR, speed, and distance were similar between HIIE RPE and HIIE HR . BP response was not different among HIIE RPE , HIIE HR , and MICE. Capillary glycaemia reduction was greater (P < 0.05) after HIIE RPE (48.6 ± 9.6 mg/dL) and HIIE HR (47.2 ± 9.5 mg/dL) than MICE (29.5 ± 11.5 mg/dL). Reduction (P < 0.05) in 24-h (6.7 ± 2.2 mm Hg) and tendency toward reduction (P = 0.06) in daytime systolic (7.0 ± 2.5 mm Hg) ambulatory BP were found only after HIIE RPE . These results suggest that HIIE is superior to MICE for reducing glycaemia and ambulatory BP, and that the 6–20 RPE scale is a useful tool for prescribing and self-regulating HIIE in individuals with T2DM.
Keywords: Arterial stiffness; Blood pressure; Capillary glycaemia; High-intensity interval exercise; Rating of perceived exertion; Type 2 diabetes mellitus